Analytical studying the axial performance of fully encapsulated rock bolts. (October 2021) - Chen, Jianhang; Liu, Peng; Zhao, Hongbao; Zhang, Cun; Zhang, Junwen
Highlights: A new analytical model was proposed for fully grouted rock bolts. Failure of the rock bolting system can be studied with this analytical method. Credibility of this analytical model was confirmed with experimental results. Abstract: Fully encapsulated rock bolts are widely used in keeping the stability of underground openings and slopes. However, bonding failure at the bolt/grout (B/G) interface still occurs. Thus, a theoretical solution was proposed to investigate the rock bolting performance. The coupling and decoupling behaviour of the B/G interface is simulated with a bonding-slipping formula. The feasibility of this bonding-slipping formula was confirmed with physical experiments on rock bolts. Then, the rock bolt loading procedures were analysed. The advantage of this theoretical model is that all input parameters can be directly acquired from the experimental pullout scenario. Three physical pullout experiments, including laboratory and field tests, were used to validate this theoretical modelling. After validation, the deduced theoretical model can calculate the rock bolting performance. Then, this model was adopted to perform the parameter analysis. The results reveal that the loading phases of the B/G interface are independent of the encapsulated length. With the increasing encapsulated length, the B/G interface encounters the elastic, elastic-debonding and debonding phases in order. Moreover, with the increasing grouting material modulus, the rock bolt shows more brittle performance.